Numerical Simulation of Natural Convection in the Air Gap of a Vertical Flat Plat Thermal Solar Collector with Partitions Attached to Its Glazing - Adel Laaraba; Abderrahmane Khechekhouche (Universitas Pendidikan Indonesia, 2018)
Heat transfer in the air gap of a vertical flat plat thermal solar collector containing partitions attached to its glazing has been studied numerically. The absorber and the glazing are kept at constant and different temperatures, while the vertical walls (insulation) were kept adiabatically. A conjugate formulation was used for mathematical formulation of the problem and a computer program based on the control volume approach and the simpler algorithm was used. The main aim of the current paper is to study numerically the effects of number of fins and their length on the air pattern and heat transfer. Experimental results showed that interesting phenomena happened, especially in the heat transfer process. It was observed that the heat transfer rate through the air gap is affected greatly and can be controlled by the number of attached fins to the glazing of the solar collector as well as the fin lengths, and the addition of partitions reduces the heat losses by convection by 60%. This study will brings good advantages for further uses, especially related to the heat transfer phenomena in the solar applications.